Comparison of Drug-Coated Balloon Angioplasty vs. Drug-Eluting Stent Implantation for Drug-Eluting Stent Restenosis in the Routine Clinical Practice: A Meta-Analysis of Randomized Controlled Trials - Zhu, Yong; Liu, Kesen; Kong, Xiangyun; Nan, Jing; Gao, Ang; Liu, Yan; Han, Hongya; Li, Hong; Zhu, Huagang; Zhang, Jianwei; Zhao, Yingxin (Frontiers in Cardiovascular Medicine, 2021)
Introduction: In-stent restenosis (ISR) remains a challenging issue despite the great advance of drug-eluting stents (DES). In addition, the consensus was lacking regarding the optimal strategy for DES-ISR. Therefore, we aimed to evaluate angiographic and clinical outcomes of the two most effective treatments DES vs. drug-eluting balloon (DCB) for patients with DES-ISR. Methods: This meta-analysis used the data from the randomized controlled trials (RCTs), which were identified by a systematic search in the databases of PubMed, Embase, and Cochrane Library. Target lesion revascularization (TLR) was regarded as the primary endpoint. In addition, the late angiographic outcomes and other clinical outcomes, namely, cardiac death, myocardial infarction (MI), target vessel revascularization, stent thrombosis, and major adverse cardiac events, were also included for analysis. Results: Five RCTs with about 1,193 patients were included in this meta-analysis for the analysis. For the primary endpoint, the overall pooled outcomes suggested repeat DES implantation was associated with a significant reduction in the term of TLR compared with DCB angioplasty (risk ratio = 1.53, 95% CI 1.15–2.04, p = 0.003). But no significant difference in angiographic outcomes and other clinical endpoints were observed between DES and DCB. In the subgroup analysis, DCB was inferior to new-generation DES (NG-DES)/everolimus-eluting stent (EES) in the term of TLR. In addition, this non-significant trend was also noted in the subgroup of the paclitaxel-eluting stent (PES) vs. DCB. For the angiographic endpoints, EES, not PES, was associated with larger minimum lumen diameter [mean difference (MD) = −0.25, 95% CI −0.38 to −0.11, p = 0.0003], lower percent diameter stenosis (MD = 7.29%, 95% CI 2.86–11.71%, p = 0.001), and less binary restenosis (OR = 2.20, 95% CI 1.18–4.11, p = 0.01). But NG-DES/EES was comparable to DCB in cardiac death, MI, and stent thrombosis. Conclusions: For the patients with DES-ISR, treatment with DES, especially NG-DES/EES could reduce the risk of TLR significantly compared to DCB at long-term follow-up.